Enhancing health literacy through co-design: development of culturally appropriate materials on genetic risk and customary consanguineous marriage. (12th April 2018) - Ali, Parveen Azam; Salway, Sarah; Such, Elizabeth; Dearden, Andrew; Willox, Matt
Abstract : Aim: To develop a simple health literacy intervention aimed at supporting informed reproductive choice among members of UK communities practising customary consanguineous marriage. Background: The contribution of 'health literacy' to reducing health inequalities and improving primary health-care efficiency is increasingly recognised. Enhancing genetic literacy has received particular attention recently. Consanguineous marriage is customarily practised among some UK minority ethnic communities and carries some increased risk of recessive genetic disorders among offspring compared with unions among unrelated partners. The need to enhance genetic literacy on this issue has been highlighted, but no national response has ensued. Instead, a range of undocumented local responses are emerging. Important knowledge gaps remain regarding how the development and implementation of culturally appropriate, effective and sustainable responses can be achieved. Methods: Our co-design approach involved active participation by local people. Initial insight generation employed six focus group discussions and 14 individual interviews to describe current understandings and information needs. A total of 11 personas (heuristic narrative portraits of community 'segments') resulted; four participatory workshops provided further understanding of: preferred information channels; feasible information conveyance; and responses to existing materials. Prototype information resources were then developed and feedback gathered via two workshops. Following further refinement, final feedback from health-care professionals and community members ensured accuracy and appropriateness. Findings: The project demonstrated the utility of co-design for addressing an issue often considered complex and sensitive. With careful planning and orchestration, active participation by diverse community members was achieved. Key learning included: the importance of establishing trusting and respectful relationships; responding to diversity within the community; and engendering a creative and enjoyable experience. The resultant materials were heavily shaped by local involvement. Evaluative work is now needed to assess impacts on knowledge and service uptake. Longer term sustainability will depend on whether innovative community-level work is accompanied by broader strategy including investment in services and professional development.